Renal artery revascularization is a controversial treatment strategy for renal artery stenosis: A case series and a brief review of the current literature - Georgios Triantis; Georgios K. Chalikias; Emmanouil Ioannidis; Anna Dagre; Dimitrios N. Tziakas (Hellenic Journal of Cardiology, 2022)
Renal artery stenosis (RAS) may cause secondary hypertension, progressive decline in renal function, and cardiac destabilization syndromes including “flash” pulmonary edema, recurrent congestive heart failure, and cerebro-cardiovascular disease. Atherosclerotic lesions, fibromuscular dysplasia, and vasculitides are the pathophysiological basis of the disease. Common therapeutic pathways for RAS include medical therapy and revascularization with or without stenting. Randomized controlled trials evaluating renal revascularization have not reported any advantages of revascularization over medical therapy alone in terms of renal function improvement or prevention of cardiovascular events. However, mounting clinical experience suggests that the best strategy in RAS management is to identify which patients are most likely to benefit from renal artery stenting and to optimize the safety and durability of the procedure. This review presents 3 cases of patients who have undergone renal revascularization and discusses the available clinical evidence for the identification of RAS patients who will potentially respond well to revascularization.